TRAF6 regulates EGF-induced cell transformation and cSCC malignant phenotype through CD147/EGFR - Zhang, Xu (Oncogenesis, 2018)
TRAF6, a well-known adapter molecule, plays pivotal role in TLR/IL-1R associated signaling pathway. Although TRAF6 has been shown to have oncogenic activity in various malignant tumors, the details remain unclear. In this study, we demonstrated that TRAF6 facilitates Ras (G12V) and EGF-induced cellular transformation through EGFR. Silencing of TRAF6 expression significantly downregulated AP-1 activity, as well as MMP-2,9 expression after EGF stimulation. Furthermore, we found that TRAF6 plays an essential role in cutaneous squamous cell carcinoma (cSCC) malignant phenotypes, affecting cell growth and migration. CD147/Basigin, a transmembrane glycoprotein belonging to the immunoglobulin superfamily, is over-expressed in tumors and induces tumorigenesis. Our results showed that CD147 formed complex with EGFR and TRAF6. Knockdown of TRAF6 disrupted the CD147-EGFR complex, thereby inducing EGFR endocytosis. Therefore, TRAF6 might be a novel molecular target for cSCC prevention or therapy.